DEVELOPING MATHEMATICS LEARNING KITS IN STATISTICS COMPETENCY BY PROBLEM BASED LEARNING APPROACH IN TERMS OF MATHEMATICS LEARNING ACHIEVEMENT FOR JUNIOR HIGH SCHOOL STUDENTS - Wulandari .; Heri Retnawati (Universitas Negeri Yogyakarta, 2017)
This study aimed to develop mathematics learning kits such as lesson plan and student worksheet by Problem Based learning approach in statistics competency for junior high school student grade VII, and to know the quality of learning kits based on validity, practicality, and effectivity aspects. This study was a developing research address to ADDIE developing model, those are Analysis, Design, Development, Implementation, and Evaluation.The quality of learning kits validity reached valid criteria, showed by mean of lesson plan validity was 4.11 from maximum score 5 with good qualification (x 4,2)and mean of student worksheet validity was 4.01 from maximum score 5 with good qualification (x 4,2).The quality of learning kits practicalityreached practicalcriteria, showed by mean of student response questionnaire was 3 from maximum score 4 with good qualification(2,8̅≤3,4), teacher response questionnairewas 3.01 from maximum score 4 with good qualification (2,8̅≤3,4), and observation result of learning activity was 95% with very good category. Beside that, the quality of learning kits saw from effecticity aspect reached effective criteria. It showed by mean of student study result test was 93.5 and its percentage of students graduationwas 100%. Keywords: learning kits, Problem Based Learning, statistics competency, student achievement.